Characterization of β2-microglobulin expression in different types of breast cancer - Li, Kesheng (BioMed Central, 2014)
BACKGROUND: Βeta-2-microglobulin (β2-M) has been demonstrated as a growth factor and signaling molecule in breast cancer and leukemia. The purpose of the study is to characterize β2-M expression in molecular subtypes of breast cancer, thereby investigating the mechanism of β2-M action in breast cancer. METHODS: β2-M and B-Cell Lymphoma/Leukemia 2 (Bcl-2) transcript expression levels in breast cancer tissue and the corresponding normal tissue were quantified using real-time PCR. The protein expression levels of β2-M, estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER-2), tumor protein 53 (p53) and Ki67 were determined by immunohistochemical (IHC) staining. Following silencing of the β2-M by siRNA, the levels of Bcl-2, ER, PR and HER-2 transcripts and the protein expression levels in human breast cancer cells were measured by real-time PCR and western blotting, respectively. RESULTS: The expression of β2-M transcripts demonstrated no significant differences between the four breast cancer molecular subtypes and no significant correlations with age, clinical stage or lymph node metastasis. β2-M transcript expression demonstrated a positive correlation when compared to Bcl-2 transcript expression (P < 0.05). The β2-M protein expression was significantly higher in breast cancer when compared with benign breast tumors (P < 0.01), and have no significant correlation with age, clinical stage or lymph node metastasis. There was a significant difference demonstrated in β2-M protein expression in the four breast cancer molecular subtypes (P < 0.05), and between the ER(+) and ER(−) groups (P < 0.01); however, no significant difference was demonstrated between the HER-2(+) and HER-2(−) groups. β2-M protein expression had a negative correlation with ER protein expression (P < 0.01), a positive correlation with p53 protein expression (P < 0.01), and no correlation with Ki67 protein expression. β2-M silencing significantly inhibited Bcl-2 mRNA expression, but did not inhibit ER, PR and HER-2 mRNA expression in MCF-7 cells (ER(+), PR(+) and HER-2(−)). In addition, Bcl-2 and HER-2 mRNA expression were significantly up-regulated in MDA-MB-231 cells (ER(−), PR(−) and HER-2(−)), which is consistent with the silencing effect seen at the protein level. CONCLUSIONS: β2-M expression demonstrated a significant difference in the four breast cancer molecular subtypes, and may be related to apoptosis regulation in breast cancer.